A fuel cell system for among unmanned aerial vehicle - HUANG ZHANGBIAO (2017)
The utility model discloses a fuel cell system for among unmanned aerial vehicle, include: aircraft administrative unit, fuel cell, DC DC converter, lithium cell, BMS power management system, electricity are transferred and direct current motor, and the aircraft administrative unit is controlled respectively fuel cell and DC the DC converter, fuel cell's output and DC the input of DC converter is connected, is the power of fuel cell output through DC DC converter conversion back is the electricity and transfers the power supply, and the electricity uses the work in drive direct current motor, is the lithium cell connected at DC through BMS power management system between DC converter and electricity were transferred, its time of endurance was long. 本实用新型公开了种用于无人机中的燃料电池系统，包括：飞机管理单元、燃料电池、DC-DC转换器、锂电池、BMS电源管理系统、电调以及直流电机，飞机管理单元分别控制所述燃料电池以及DC-DC转换器，燃料电池的输出端与DC-DC转换器的输入端连接，燃料电池输出的电源经DC-DC转换器转换后为电调供电，电调用于驱动直流电机工作，锂电池经BMS电源管理系统连接在DC-DC转换器与电调之间，其续航时间长。